Abscessed apical radicular cyst. Case report - Yailenis Francés Rodríguez; Lianne Laura de León Ramírez; Carlos Enrique Medina Campaña; Adriana María Barroso de la Cruz (Universidad de Ciencias Médicas de Granma, 2021)
Introduction: the apical radicular cyst is the most frequent within the odontogenic cysts of the oro-maxillofacial region, with a prevalence of 90%. It occurs in the permanent dentition, mainly in the anterior area and they are usually asymptomatic, as long as they are not associated with inflammatory processes. Case presentation: a 36-year-old male patient with a medical history who presented to the Maxillofacial Surgery consultation, reporting intense pain in the area of the upper right teeth and increased volume in the palate with a 2-year evolution period. When performing the intraoral physical examination, teeth 12 and 13 were observed with the presence of deep caries with pulp involvement and in 14 displaced fillings. There was also an increase in volume in the region of the palate with a hard elastic consistency, painful on palpation and without a tendency to limitation, related to these teeth. Radiography and a computerized axial tomography were indicated, the results of which allowed us to arrive at the presumptive diagnosis of an apical radicular cyst, which was later corroborated by histopathological analysis. Conclusions: In clinical practice, radicular cysts are found fortuitously through imaging studies, since most are asymptomatic. It should be borne in mind that acute pain and the absence of pulp vitality correspond as forms of presentation of this pathology, which is why a correct examination of the patient is necessary to make a timely diagnosis.